Merilni pristop za optimizacijo ogrevanja jekel v kontinuirni peči - Glogovac, Branislav (Materiali in tehnologije, 2002)
The results of measurements on a walking-beam furnace for billet reheating are presented. After reconstruction of the billet transport system it was possible to change the existing operating practise with three furnaces to operate with only one furnace. For this purpose it was necessary to improve the measurement and control system and to install a new monitoring system. The optimisation of the parameters in individual zones of the furnace during normal production and scheduled or unscheduled delays were possible. All control measurements on the furnace were made without any disturbing influence on the furnace is normal operation. Using steel probes, which were transported with the billets, the amount and properties of the scale were analysed. The high- and low-temperature oxygen sensor and fuel-gas analysers were used. With a minimal excess of combustion air on a burner the oxygen content in exhaust gases was between 1 and 2 %. With this air/fuel ratio within all furnace zones and pressure in soak zone 10 Pa the scale fall off very easily. Depending on the steel quality, operating temperatures and throughput rate, the differences in oxygen concentrations have a significant influence on the quality, operating temperatures and throughput rate, the differences in oxygen concentrations have a significant influence on the amount and properties of the scale.
Keywords: koračna peč; gredice; ogrevanje; meritve; optimiranje